Bio-electrochemical Denitrification -A review - Mousavi, S.A.R.; Ibrahim, S.; Aroua, M.K.; Ghafari, S. (World Academy of Research and Publication, 2011)
Discharge of nitrogen components into the environment can be a cause of serious problems such as eutrophication of rivers and deterioration of water sources, as well as hazard for human and animal health. Ammonia (NH3) and nitrate (NO3-) are the most problematic nitrogen compounds in water and wastewaters. Nitrification is a common way to eliminate ammonia in municipal and industrial wastewater, which during this process ammonia oxidizes to nitrate. Nitrate removal from these types of wastewaters is an inevitable step in the treatment. Biological nitrate removal is a suitable but slow method to remove nitrate from water and wastewater. Therefore, in treatment plants, some abiotic methods have been commonly applied. However, these methods have indicated some drawbacks such as highly concentrated brine solution, which compels complexity for further treatment or disposal. Consequently, efforts have focused on speeding up microbial denitrification techniques, and different methods have been investigated in the last two decades. Among them bio–electrochemical reactors (BERs) which are equipped with immobilized autohydrogenotrophic microorganisms on cathode showed good efficiency for implementation of denitrification for any nitrate–contaminated water stream. This article reviews the diversity of nitrate source, various designs, and aspects of BERs. In addition, it discusses the variation of pH, carbon source, electric current (EC) and hydraulic retention time (HRT) as some main effective parameters on denitrification rates, and different configurations of BERs.